Impact of stress and anxiety on dietary habits and academic performance among pharmacy students - Ibraimi, Zana; Voca, Shpend; Nuhii, Nexhibe; Murtezani, Ardiana (Progress in Nutrition, 2025)
Background and aim: Most students experience stress and anxiety during their studies. The rigorous academic schedule of coursework and exams, financial challenges, family problems, may increase the stress and anxiety even more, resulting in poor academic performance. The purpose of this study was to examine levels of stress and anxiety among students during the exam period and to analyze whether they consume more (or not) food under stress, the types of food they consume under stress, types of stressors and coping strategies, and also the impact of stress on academic performance.Methods: A cross-sectional study was conducted from June to July 2024, in a random sample of 165 undergraduate pharmacy students of the University of Pristina. A self-administered questionnaire was employed with the sociodemographic data, anthropometric and medical data, items regarding their stress and anxiety level, and dietary habits under stress and anxiety.Results: About 83% of students were female and 17% were male. The mean age of students was 22 years. Most of them (61.8%) reported that they have entered more than 3 exams in the last month, 33% entered 1-3 exams, and 8 students did not enter any exam. The average grade of students up to the time the questionnaire was administered was 8.14 (8.13 of female students and 8.18 of male students) in a scale from 5 (failure) to 10 (excellent). Sweets were among the most frequently consumed foods, followed by salty and fast food.Conclusions: Pharmacy students reported experiencing stress and anxiety during exam time a moderate level than normal, and during this time they practiced unhealthy eating habits. There was negative correlation between stress/anxiety and average grade and a positive correlation between stress/anxiety and sweets, salty foods, and fast food. Stress/anxiety were negatively correlated with body weight.